2021
DOI: 10.1163/15685403-bja10116
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and connectivity of the spiny lobster, Panulirus spp.: case studies from Brazil and the Wider Caribbean (Decapoda, Achelata)

Abstract: In this study, we look at recent developments in our understanding of the life cycle of the red spiny lobster Panulirus argus (Latreille, 1804) and examine the evidence for connectivity between geographical regions, especially the north-northeast Brazilian continental shelf and the Wider Caribbean. The study also covers aspects of reproduction, phyllosoma density, large-scale oceanic circulation, self-recruitment, settlement patterns, ecological behaviour, and the impact of the Amazon and Orinoco river dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…In addition to the competition with the anthozoan Palythoa caribaeorum 65 , the arrival of sun-coral larvae in the region can affect the survival of Brazilian endemic coral species such as Siderastrea stellata, Favia gravida , and Mussismilia hispida 66 . Successful colonization of this system may intensify the sun-coral invasion process of the Caribbean Sea due to the ecological connectivity of this region with the Brazilian biogeographical province 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the competition with the anthozoan Palythoa caribaeorum 65 , the arrival of sun-coral larvae in the region can affect the survival of Brazilian endemic coral species such as Siderastrea stellata, Favia gravida , and Mussismilia hispida 66 . Successful colonization of this system may intensify the sun-coral invasion process of the Caribbean Sea due to the ecological connectivity of this region with the Brazilian biogeographical province 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%
“…in the north-northeast Brazilian continental shelf and the Wider Caribbean revealed potential hybridization between closely located lobster species, demonstrated through distinctions in colour patterns and physical features. 88 4.1.2 | Distinguishment of natural interspecific hybridization of shrimps, lobster, crayfish and crabs by molecular methods Since morphological differences can be influenced by the environment, they can be mistakenly used as criteria to delimit species, as seen in the southern king crabs, Lithodes santolla and Lithodes confundens in sub-Antarctic South America 73 or in the squat lobster, Munida gregaria and Munida subrugosa. 74 The southern king crabs, L. santolla and L. confundens were believed to be distinct based on the number and size of spines on the carapace and pereiopods, but genetic analysis demonstrated that they are not clearly separated, emphasizing the necessity for reevaluation and the application of genetic methods in fisheries management.…”
Section: Distinguishment Of Natural Interspecific Hybridization Of Sh...mentioning
confidence: 99%
“…The study of life cycle and connectivity of the spiny lobster ( Panulirus spp.) in the north‐northeast Brazilian continental shelf and the Wider Caribbean revealed potential hybridization between closely located lobster species, demonstrated through distinctions in colour patterns and physical features 88 …”
Section: Hybridization In Decapod Crustaceanmentioning
confidence: 99%
“…The transport of larvae by the North Brazilian Current has also been proposed to explain the maintenance of the shrimp popula-tion (Farfantepenaeus subtilis) in French Guiana [62], as well as spiny lobster (Panulirus spp.) throughout the Caribbean [63].…”
Section: Proposal Of Goliath Grouper Life Cycle In French Guianamentioning
confidence: 99%